Addressing Tax Arbitrage with Hybrid Financial Instruments : a Multidisciplinary Study and Proposal for Developed and Developing Countries. - Scherleitner, Moritz (Doctoral series, 2020)
Analysing legislative action against tax arbitrage with hybrid financial instruments from a multidisciplinary perspective, this book provides valuable insight into the effects of potential approaches.